Tri Hita Karana as the foundation for digital game development - Saskara, I Putu Adi (Institut Seni Indonesia Surakarta, 2024)
This research aims to develop a digital game based on the Tri Hita Karana concept to introduce and instill Balinese cultural values in children. Tri Hita Karana, which includes the harmonious relationship between humans and God (Parahyangan), humans and fellow humans (Pawongan), and humans and nature (Palemahan), is integrated into digital games to teach ethical and moral values. This research uses a qualitative approach with Husserl's phenomenological method, which is designed to explore in-depth information about the feasibility of the Tri Hita Karana concept as a basis for digital game development. Data collection was carried out through in-depth interviews, observation and documentation determined by the purposive sampling method. The research results show that the Tri Hita Karana concept is very relevant and effective as a basis for developing educational digital games. The values contained in Tri Hita Karana can be implemented into game features that encourage players to work together, protect the environment, and develop morality. The game